2017
DOI: 10.1038/srep43830
|View full text |Cite
|
Sign up to set email alerts
|

Computational Modeling of complete HOXB13 protein for predicting the functional effect of SNPs and the associated role in hereditary prostate cancer

Abstract: The human HOXB13 gene encodes a 284 amino acid transcription factor belonging to the homeobox gene family containing a homeobox and a HoxA13 N-terminal domain. It is highly linked to hereditary prostate cancer, the majority of which is manifested as a result of a Single Nucleotide Polymorphism (SNP). In silico analysis of 95 missense SNP’s corresponding to the non-homeobox region of HOXB13 predicted 21 nsSNP’s to be potentially deleterious. Among 123 UTR SNPs analysed by UTRScan, rs543028086, rs550968159, rs56… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 79 publications
(118 reference statements)
0
17
0
Order By: Relevance
“…Recently, an in silico analysis suggested that the deleterious HOXB13 variants increase the stability of the HOXB13 protein, overexpressing the genes responsible for cell proliferation and growth as RFX6. 16 Among the inclusion criteria was ancestry, thus all subjects were of Martinican descent. The Martinican population consists mainly of African people (>90%) with some interbreeding with French Caucasian.…”
Section: Previousmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, an in silico analysis suggested that the deleterious HOXB13 variants increase the stability of the HOXB13 protein, overexpressing the genes responsible for cell proliferation and growth as RFX6. 16 Among the inclusion criteria was ancestry, thus all subjects were of Martinican descent. The Martinican population consists mainly of African people (>90%) with some interbreeding with French Caucasian.…”
Section: Previousmentioning
confidence: 99%
“…Furthermore, the knockdown of HOXB13 would inhibit cell proliferation of ovarian tumors. Recently, an in silico analysis suggested that the deleterious HOXB13 variants increase the stability of the HOXB13 protein, overexpressing the genes responsible for cell proliferation and growth as RFX6 16 . A previous study by Huang et al 17 demonstrated that the RFX6 variant (rs339331) might influence the expression of RFX6 by increasing binding of HOXB13 to transcriptional enhancer.…”
Section: Introductionmentioning
confidence: 99%
“…Whether the G84E mutation affects the HOXB13-AR interactions remains elusive. From computational analyses, it is predicted that the mutation results in damaging and deleterious effects on HOXB13 DNA-binding capacity and increased stability of its protein structure (Chandrasekaran et al 2017). While hereditary HOXB13 mutations have been extensively reported in tissue, it remains to be determined whether this mutation affects HOXB13 and/or AR chromatin binding in vitro.…”
Section: Hoxb13mentioning
confidence: 99%
“…The mutation frequency spectrum of CDH23 among the recessive inherited cases is 5.7% in the Japanese population and 15% in the Korean population [16,19,49]. Other gene variants were also analyzed using such programs such as V66 M variant of human BDNF in psychiatric disorders and computational modeling of complete HOXB13 protein for predicting the functional effect of SNPs and the associated role in hereditary prostate cancer [50,51]. The American College of Medical Genetics and Genomics (ACMG) guide for the interpretation of sequence variants elaborated the usefulness of the predictive software programs for risk estimation and accurate interpretation of the potential causality of sequence variation [52].…”
Section: Discussionmentioning
confidence: 99%